The concept and principles of social responsibility in the moral and legal dimension - Vasilevich, Sergey Grigorievich (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право»)
Introduction. The article analyzes doctrinal definitions of social responsibility and its principles, constitutional legislation of the Russian Federation and the Republic of Belarus. Theoretical analysis. It is emphasized that in scientific literature the predominant attention is paid to corporate social responsibility. The author solidarizes with the position according to which social responsibility is the most important condition for sustainable development of the state. The author focuses on the content of such principles of corporate activity as accountability and transparency of activity, accessibility and comprehensibility of information about the organization’s activity; honesty, fairness, integrity of its behavior, respect for and consideration of the interests of stakeholders and others. Result. The content of the principles of social responsibility is disclosed. The author’s definition of social responsibility is formulated: everyone’s social responsibility is an internally conscious behavior of the relevant subject, reflecting the desire to benefit society and the state, as well as supported by the force of legal or social influence, the use of the participant of social relations of his or her abilities to meet not only personal interests, but also for the public good, taking into account the available intellectual, physical, material and other resources.